The Metabolic Mechanisms of Breast Cancer Metastasis - Wang, Lingling; Zhang, Shizhen; Wang, Xiaochen (Frontiers in Oncology, 2021)
Breast cancer is one of the most common malignancy among women worldwide. Metastasis is the leading cause of treatment failure and is responsible for the majority of breast cancer mortality. In addition to genetic alterations, metabolic reprogramming plays an important role in breast cancer progression and metastasis. However, the regulatory mechanisms that contribute to cancer metastasis by metabolic reprogramming in breast cancer have not been fully elucidated. Breast cancer cells exhibit different metabolic phenotypes depending on their molecular subtypes and metastatic sites. Both intrinsic factors, such as MYC amplification, PIK3CA, and TP53 mutations, and extrinsic factors, such as hypoxia, oxidative stress, and acidosis, contribute to different metabolic reprogramming phenotypes in metastatic breast cancers. Understanding the metabolic mechanisms underlying breast cancer metastasis will provide important clues to develop novel therapeutic approaches for treatment of metastatic breast cancer.